1997
DOI: 10.1111/j.1442-200x.1997.tb03748.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum zinc, copper, and magnesium levels in obese children

Abstract: Serum zinc, copper and magnesium levels were measured using atomic absorption spectrophotometry in 41 obese and 41 healthy (control) children (between 7 and 11 years of age) who were living in Malatya (Turkey). Serum zinc levels of obese children (mean value 102.40 f 2.78 pg/dL) were found to be significantly higher than those of the control group (mean value 80.49 f 2.98 pg/dL; P < 0.01). Serum copper concentrations were also found to be significantly higher in obese children (mean value 132.34 f 1.79 pg/dL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 5 publications
5
26
1
Order By: Relevance
“…From this point of view, insufficient iron may be affected not only the BMI but also cognitive performance in adolescent girls. Furthermore, our results agree with others [11][12][13][14][15][16] that people with higher BMIs have lower magnesium and zinc concentrations in their hair.…”
Section: Disscusionsupporting
confidence: 93%
See 1 more Smart Citation
“…From this point of view, insufficient iron may be affected not only the BMI but also cognitive performance in adolescent girls. Furthermore, our results agree with others [11][12][13][14][15][16] that people with higher BMIs have lower magnesium and zinc concentrations in their hair.…”
Section: Disscusionsupporting
confidence: 93%
“…4,[12][13][14] Martino et al 15) conducted studies on the concentration of 17) used this equipment to analyze the concentration of metal in blood samples of Taiwanese residents. There is only limited research on the analysis of hair samples from young women (age from 15 to 19 years) with the different BMIs to determine calcium, copper, iron, magnesium, and zinc concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Serum magnesium and dietary magnesium were inversely associated with IR, providing the first evidence that the association between magnesium deficiency and IR is present during childhood. These associations were not evaluated in previous studies that measured serum or intracellular magnesium in obese children (16,17) but agree with studies in adults that found that low serum magnesium concentrations are associated with hyperinsulinemia, decreased insulin-mediated glucose disposal, and the metabolic syndrome (4,5,18). In the Atherosclerosis Risk in Communities study, Caucasian men with serum magnesium Ͻ0.58 mmol/l had a twofold increase in incidence of type 2 diabetes compared with those with a magnesium concentration Ͼ0.78 mmol/l (8).…”
Section: Subanalysis In Race-matched Pairsmentioning
confidence: 96%
“…In general malnutrition and long term diarrhoea, it has been notified that there are low serum copper levels. In spite of malnutrition, it has been demonstrated that high serum copper levels in obese children could be due to their good appetite [37]. But no studies have been come across to have examined the relationship between drinking water copper levels and fat tissue formation in women aged 55-70.…”
Section: Discussionmentioning
confidence: 99%